Complex Treatment III class of gum recession - L. A. Ananieva; G. S. Runova (LLC "Endo Press", 2020)
The recessions of the 3 Miller class are the most difficult in the prediction of the result during surgical treatment. Such recession in the anterior region of the mandible is often combined with a small vestibule of the oral cavity. The treatment of combined pathology in the standard protocol was provided in 2 stages: correction of small vestibule of the oral cavity and elimination of the recession by the method of the coronal advanced flap.Aim. To develop the protocol of one-stage operation for patients with III miller class gum recession in combination with small vestibule.Materials and metods. Surgical protocole. after conducting anesthesia at the region of the lower teeth held tunnel access to the region of teeth with gingival recession, formed split-thikness flap, discharge below the periodontal line connection 3 mm, mobilization of the flap.The flap is fixed with sutures Polyprophylene 6-0. Taken from the palatal free gingival graft. Placed in the region of holding vestibuloplasty fixed to the periosteum of the simple suture and suturing the donor area in the palate.Results. The patients were found to have closing of the recession, the increase in the area keratinisation gums and keeping of the vestibule in the recovery area.Conclusions. The development of a new one-stage treatment of recession 3 class at Miller in combination with vestibuloplasty allows you to more quickly treat patients with this pathology.